Близкий друг: [роман] / сестры Воробей - Сестры Воробей (Романы для девочек, 2003)
Экземпляры: (20181023) / Инвентарный номер: 30092 / Цена: 14.00 / Сис.шифр: Р2 / Авт.знак: В 75 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6